Factors influencing grade 1 school placement and subsequent changes in school placement of learners with cochlear implants - Bardien, Faeza (Stellenbosch : Stellenbosch University, 2008)
Thesis (MAud (Interdisciplinary Health Sciences. Speech-Language and Hearing Therapy)--Stellenbosch University, 2008.